Migrasome, a novel organelle, differs from exosomes - Xun Tan; Shujin He; Fuling Wang; Lei Li; Wei Wang (Biochemistry and Biophysics Reports, 2023)
Migrasomes, a newly discovered organelle produced by migrating cells, are vesicles with membranous structure that form on the tips and intersections of retraction fibers (RFs). These structures are released into the extracellular environment or taken up by surrounding cells, mediating the release of cytoplasmic contents and intercellular communication. Retractosomes, a new type of small extracellular vesicles generated from broken-off RFs, are closely related to migrasomes in their physical location and origin, but were defined later. Despite their widespread existence in cells and biological organisms, little is known about the regulatory mechanisms underlying their formation and potential function. In this review, we provide an overview of the discovery, biogenesis, distribution, and functions of migrasomes and retractosomes, as well as their differences from exosomes.